Occupational Stress and Caring Behavior Among Nurses in a Private Hospital in Henan, China - Yuan, Songbo; F. Lazaro, Leslie (Journal of Neonatal Surgery, 2025)
The research team conducted their study by measuring both occupational stress and caring behavior of hospital staff nurses at private medical facilities in Henan Province China. The research evaluated staff nurse perceptions of occupational stress and caring behavior together with their relationship patterns and determined what impact age, sex, marital status and work experience at the hospital had on these variables. A descriptive-correlational research approach supported the study that selected 309 nurses through stratified random sampling methods. Three primary sections were incorporated in the validated questionnaire that employed for data collection: demographic profile as well as occupational stress domains across six areas together with caring behavior dimensions across three areas. Internal reliability of the questionnaire measured by Cronbach's alpha value exceeded 0.85. Consistent analysis of the data included descriptive statistics and Pearson's correlation and chi-square tests and normality tests. Staff members from the surveyed group showed mostly medium-high occupational stress which increased most prominently regarding their workload conditions and their limited availability for leave. Research results demonstrated that occupational stress showed a substantial positive relationship (r =0.964) at p < 0.001 with caring behavior. Single and inexperienced nurses under the age of 30 exhibit lower levels of caring behavior on the nursing attitude scale. The research findings indicate reduction of occupational distress through purposeful interventions leads to enhanced nursing care practices. The data shows that institutional reforms with subsequent studies should be implemented.